Working with polynomial: (6x^2 - 25x - 10) / (3x + 2)

(6x^2 - 25x - 10) / (3x + 2) = (6x^2/3x+2) - (25x/3x+2) - (10/3x+2) = 2x - 29/3 R. 28/3

s

Question

Asked 12/13/2010 3:54:20 AM

Updated 7/27/2014 12:19:20 PM

1 Answer/Comment

Edited by andrewpallarca [7/27/2014 12:18:08 PM]

Rating

3

(6x^2 - 25x - 10) / (3x + 2)

= (6x^2/3x+2) - (25x/3x+2) - (10/3x+2)

= 2x - 29/3 R. 28/3

= (6x^2/3x+2) - (25x/3x+2) - (10/3x+2)

= 2x - 29/3 R. 28/3

Added 7/27/2014 12:19:20 PM

This answer has been confirmed as correct and helpful.

Working with polynomial: (8x – 5) + (7x + 4) **Weegy:**
(8x – 5) + (7x + 4)
= 8x + 7x - 5 + 4
= 15x - 1
(More)

Question

Expert Answered

Updated 41 days ago|6/23/2020 6:24:21 AM

0 Answers/Comments

Working with polynomial: (5x – 3.6) – (4x + 1.2)

Question

Expert Answered

Updated 7/3/2014 1:57:21 PM

1 Answer/Comment

Working with polynomial: (3x^2 + 3x) + (4x + 4). Please show the steps on how you got your answer. Thanks!

Question

Updated 8/10/2014 5:55:48 PM

1 Answer/Comment

(3x^2 + 3x) + (4x + 4)

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

Added 8/10/2014 5:55:48 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/10/2014 5:57:18 PM]

31,980,073

questions answered

There are no comments.